The Strategies to Improve Teachers’ Performance through Workshop Activities at MTsN - Deni Khurniawan; Makmur Syukri; Amiruddin Siahaan; Yulita Suyatmika (Universitas Pahlawan Tuanku Tambusai, 2022)
Teachers are partners for child development. On this basis, government policies favor efforts to improve teacher welfare, creativity, and teacher competence. This study seeks to describe strategies for improving teacher performance through workshop activities at MTsN 4 Mandailing Natal. This type of research includes classroom action research (CAR) as an effort to improve education from classrooms. The research subjects are 20 teachers who teach class VIII students (with various fields of study) for the 2021/2022 academic year. Analysis of research data based on quantitative methods using questionnaires and observations. It is carried out in components of 2 (two) cycles, covering the stages of planning, implementing, observing, and reflecting. The results of this study indicate that the strategy for improving teacher performance is very well implemented through a workshop at MTsN 4 Mandailing Natal. This is viewed from the core aspects of learning to be able to apply learning that there are no people or 0.00% teachers (not good category), 1 person or 5.00% of teachers are classified as sufficient, 6 people or 30.00% are classified as good and 13 people or 65.00% is classified as very good. If the sum of those categorized as good and very good reaches 19 people or 95.00%, understanding of learning strategies can be improved both in theory (conceptual) and implementation (contextual).